The effect of bone lavage on femoral cement penetration and interface temperature during Oxford unicompartmental knee arthroplasty with cement - Seeger, Jörn Bengt; Jäger, Sebastian; Bitsch, Rudi G.; Mohr, G.; Röhner, E.; Clarius, Michael (The journal of bone & joint surgery. A, American volume, 2013)
Background: Aseptic loosening is the most common cause for revision unicompartmental knee arthroplasty and is associated with failure of the bone-cement or cement-implant interface. The purpose of the present study was to analyze different bone lavage techniques for the bone-cement and cement-implant interfaces of the femoral component and to study the effect of these techniques on cement penetration and on interface temperature. - Methods: In an experimental cadaver study, Oxford unicompartmental knee arthroplasty was performed in twenty-four matched-paired knees to study the effect of pulsed lavage compared with syringe lavage on femoral cement penetration and interface temperature. Interface temperature, cement penetration pressure, and ligament tension forces were measured continuously during the procedure, and cement penetration was determined by performing sagittal bone cuts. - Results: Cleansing the femoral bone stock with use of pulsed lavage (Group B) led to increased femoral cement penetration (mean, 1428 mm2; 95% confidence interval, 1348 to 1508 mm2) compared with syringe lavage (Group A) (mean, 1128 mm2; 95% confidence interval, 1038 to 1219 mm2) (p < 0.001). Interface temperature was higher in Group B (mean 22.6°C; 95% confidence interval, 20.5°C to 24.1°C) than in Group A (mean, 21.0°C; 95% confidence interval, 19.4°C to 23.0°C) (p = 0.028), but temperatures never reached critical values for thermal damage to the bone. - Conclusions: Pulsed lavage leads to an increased femoral cement penetration without the risk of heat necrosis at the bone-cement interface. - Clinical Relevance: Pulsed lavage techniques should be strongly considered for use as a routine procedure for unicompartmental knee arthroplasty with cement to increase bone cement penetration of the implant.